2019
DOI: 10.1080/14397595.2018.1520426
|View full text |Cite
|
Sign up to set email alerts
|

New adalimumab formulation associated with less injection site pain and improved motivation for treatment

Abstract: The new ADA formulation may alleviate the burden on RA patients and improve the quality of adherence to treatment, thereby influencing the RA treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…In the current study, significantly decreased ISP was reported with FKB327 compared with CCF-RP, which may be due to the citrate buffer that is present in CCF-RP but not in FKB327, as an association between citrate buffer and ISP has been demonstrated previously [9]. Results have shown that a citrate-free formulation of the RP was associated with significantly decreased ISP [29,30]. Therefore, the results of the current study support previous findings demonstrating an association between a decreased level of ISP and citrate-free formulations.…”
Section: Multiple-dose Studiessupporting
confidence: 63%
“…In the current study, significantly decreased ISP was reported with FKB327 compared with CCF-RP, which may be due to the citrate buffer that is present in CCF-RP but not in FKB327, as an association between citrate buffer and ISP has been demonstrated previously [9]. Results have shown that a citrate-free formulation of the RP was associated with significantly decreased ISP [29,30]. Therefore, the results of the current study support previous findings demonstrating an association between a decreased level of ISP and citrate-free formulations.…”
Section: Multiple-dose Studiessupporting
confidence: 63%
“…Studies have shown that in patients with subcutaneous injection stimulating pain, VAS scores can reach more than 7 points. 30 In this study, a significant proportion of patients with positive pain at the injection site experienced moderate or higher pain. In addition to acute pain, deep fascia lesions might also trigger pain sensitivity and CPSP.…”
Section: Discussionmentioning
confidence: 62%
“…In this study, we compared a 100-mg/mL, citrate-free formulation of proposed biosimilar AVT02 with recent batches of reference originator adalimumab product. The 100-mg/mL, citrate-free originator adalimumab is the most current formulation, one that augments the administration of originator adalimumab by reducing injection pain [ 10 , 20 ].…”
Section: Discussionmentioning
confidence: 99%